CROWDSOURCING TECHNOLOGIES FOR DEVELOPING CIVIL ACTIVITY IN RUSSIA (ON THE EXAMPLE OF THE PROJECT «ACTIVE CITIZEN») - E. Yudina; S. Zakharova (Вестник университета, 2016)
The article considers how crowdsourcing is used in the sphere of the public and municipal administration on the example of the Project «Active Citizen». The paper describes authors’ sociological research and analysis of features of network interaction of the regional authorities, the conclusion about possibility of crowdsourcing application for increase of social citizen activity is drawn.